Monitoring training load in runners, throwers and sprinters/jumpers during a preparatory training camp - Cristina-Souza, G.; Mariano, A. C. S.; Souza-Rodrigues, C. C.; Santos, P. S.; Bertuzzi, R.; Lima-Silva, A. E.; de Oliveira, F. R. (Journal of Physical Education and Sport, 2019)
Problem Statement: The rating of perceived exertion has been widely used to quantify training load during a given training session. Athletes of different modalities might differently respond to a given imposed training load. Purpose: The present study compared training load responses between runners, throwers and sprinters/jumpers. Methods: Ten young men (19.1 ± 2.2 years) and eight women (18.6 ± 1.1 years), who were athletes of running (n = 6), throwing (n = 5), and sprint/jump (n = 7) events, participated in this study. The athletes performed their training routine for one week with the rating of perceived exertion registered 30 minutes after each training session. Training impulse, monotony, and strain were calculated from the rating of perceived exertion and training duration. Results: The training impulse score was similar between the groups (p > 0.05). However, training monotony and strain were higher in runners compared to throwers (p <0.05), but similar between runners and sprinters/jumpers and between throwers and sprinters/jumpers (p > 0.05). Conclusions: Even with similar training impulse, athletes of different modalities respond differently to the imposed training load. Our results suggest that runners have a higher training monotony and strain, compared to throwers. This might help coaches to understand the particularities of training modalities and therefore avoid maladapted response.